(untitled) (Plant Tissue Culture and Biotechnology, 2020)
Of the five explants viz., shoot tip, nodal segment, leaf disc, cotyledon and root tip excised from exegenic seedlings of Citrus indica Tanaka shoot tip cultured in MS supplemented with 0.5 mg/l of BAP generated shoots within 4.74 days, exhibiting highest percentage of response (85.82%) with highest number of shoots (8.9) and shoot length (3.04 cm). On the other hand nodal segment cultured in MS supplemented with 1.0 mg/l BAP showed 80% response in 5.16 days with a shoot number of 5.41 and shoot length of 2.43 cm. Cotyledon explants inoculated on MS supplemented with1.0 mg/l of TDZ produced shoots in 20 days with the highest response of 69.88%, with 3.77 shoots per cotyledon and shoot length of 2.03cm. Viable callus was obtained from leaf disc cultured on half strength MS medium with less Ca++ with 2, 4-D 0.5 mg/l + Kn 0.25 mg/l. This callus when inoculated on half strength MS medium with Kn 1.5 mg/l showed highest shoot bud proliferation of 66.66% with 10.06 shoots per callus. Root tip explant failed to produce any shoots. In vitro raised shoots of Citrus indica when cultured on half strength MS medium supplemented with NAA (1.0 mg/l) showed 80 % rooting in 5.66 days, with highest number of roots (6.16 per shoot) and longest root (3.78cm). Ninety per cent of in vitro rooted plantlets of Citrus indica survived in open conditions. Plant Tissue Cult. & Biotech. 30(1): 87-96, 2020 (June)